Implementation of Islamic Educational Practices within Families and Their Association with Student Mental Health - Fahmi Mandala Putra; Fajri Ismail; Asri Karolina; Muhammad Sirozi (Jurnal IPTEK Bagi Masyarakat, 2026)
Student mental health is a public health issue influenced by family and psychosocial factors. This study examined the relationship between Islamic education in the family and the mental health of 100 vocational high school students in Palembang, Indonesia. Using a quantitative cross-sectional design, data were collected through structured questionnaires and analyzed using descriptive statistics, Pearson correlation, independent t-test, and simple linear regression. The results showed that Islamic education in the family was generally well implemented, with moral education showing the highest distribution. Students’ mental health was also mostly in the good category, although inner peace remained the weakest aspect. Male students and those aged 17–19 years had higher mental health scores, with moderate effect sizes. Family Islamic education had a positive and significant relationship with student mental health (p < 0.05) and contributed 7.5% to its variance, while 92.5% was explained by other factors. These findings indicate that Islamic education in the family may support students’ mental health, although broader psychosocial factors remain more dominant. Therefore, parents, schools, and families need to strengthen open communication, religious values, intellectual development, physical education, and psychosocial support to reduce academic stress, especially among female students and those aged 15–16 years.